Verrucomicrobia of the Family Chthoniobacteraceae Participate in Xylan Degradation in Boreal Peat Soils - Andrey L. Rakitin; Irina S. Kulichevskaya; Alexey V. Beletsky; Andrey V. Mardanov; Svetlana N. Dedysh; Nikolai V. Ravin (Microorganisms, 2024)
The phylum Verrucomicrobiota is one of the main groups of soil prokaryotes, which remains poorly represented by cultivated organisms. The major recognized role of Verrucomicrobiota in soils is the degradation of plant-derived organic matter. These bacteria are particularly abundant in peatlands, where xylan-type hemicelluloses represent one of the most actively decomposed peat constituents. The aim of this work was to characterize the microorganisms capable of hydrolyzing xylan under the anoxic conditions typical of peatland soils. The laboratory incubation of peat samples with xylan resulted in the pronounced enrichment of several phylotypes affiliated with the Verrucomicrobiota, Firmicutes, and Alphaproteobacteria. Sequencing of the metagenome of the enrichment culture allowed us to recover high-quality metagenome-assembled genomes (MAGs) assigned to the genera Caproiciproducens, Clostridium, Bacillus (Firmicutes), and Rhizomicrobium (Alphaproteobacteria), Cellulomonas (Actinobacteriota) and the uncultured genus-level lineage of the family Chthoniobacteraceae (Verrucomicrobiota). The latter bacterium, designated “Candidatus Chthoniomicrobium xylanophilum” SH-KS-3, dominated in the metagenome and its MAG was assembled as a complete closed chromosome. An analysis of the SH-KS-3 genome revealed potential endo-1,4-beta-xylanases, as well as xylan beta-1,4-xylosidases and other enzymes involved in xylan utilization. A genome analysis revealed the absence of aerobic respiration and predicted chemoheterotrophic metabolism with the capacity to utilize various carbohydrates, including cellulose, and to perform fermentation or nitrate reduction. An analysis of other MAGs suggested that Clostridium and Rhizomicrobium could play the role of primary xylan degraders while other community members probably took advantage of the availability of xylo-oligosaccharides and xylose or utilized low molecular weight organics.